Urban freight logistics in Panama city - Castillo, Sara (Universidad Tecnológica de Panamá ; Georgia Institute of Technology, 2011)
Urban freight is the study of the flow of all goods within a specific urban area destined to satisfy its demands. This field is important because it contributes to the economic growth and development of a region. Because, an efficient urban freight system, contributes to the economic delivery of goods and improves business services. Over the last ten years, private and government institutions have performed studies to address road congestion for urban passenger transport in Panama City. However, freight transportation has not been considered within these projects and has played the role of an observer that should adapt to the existing infrastructure. This project considers "Panama City" as the region formed by the districts of Panama and San Miguelito. The general objective of this research is to estimate urban freight behavior in Panama City, in order to provide the first comprehensive study on urban freight logistics and identify the trend of freight vehicle growth for future research on infrastructure needs. This project is divided in two main deliverables: the Descriptive Assessment and the Urban Freight Network. The descriptive assessment evaluates urban freight characteristics by using four aspects: commodities, infrastructure, transport and traffic services. Commodities describe the type of freight moving in and out of the city. In order, to analyze their movement, this will be divided in: sources, sinks and paths. Sources are points of entry or exit of freight in Panama City (these are bridges, industrial parks, airports and ports). In 2010, Cristobal Port had the largest volume of truck trips for imported freight, while the Tocumen International Airport had the largest volume for exported freight. Sinks are freight consumption points, these represent the counties within the districts of Panama and San Miguelito. In 2008, the largest expenditure of the population in Panama City was food and beverages. Paths are the types of freight that move in the commodity network. Freight was divided in: national produce, imports and exports. Panama City road infrastructure is composed of three roadways: longitudinal roads, transverse streets and corridors (tolled highways). These infrastructures are the main traffic paths and connect the suburbs (San Miguelito) with the commercial areas in the district of Panama. Given that this road infrastructure is limited, this network is the primary means of transport for private, public and commercial vehicles. Panama City has 77% of the country's total vehicle count; this vehicle proportion is related to the high concentration of population and businesses in this area. The 19% of the total country's vehicle count is represented by urban freight vehicle population (fleet size). In 2010, trucks and delivery vans were the preferred urban freight vehicles in Panama City. At present there are no established regulations for the control of urban movements in the city or the country. Currently, urban movements are delimited by the combination of three main regulations: freight vehicle permitted tonnage and dimensions, general transit regulations for all types of vehicles that include cargo handling measures, and security procedures at weight control stations. The deliverable Urban Freight Network is composed of the fleet size forecast model, and the Tactical and Strategic Analysis. The tactical and strategic analyses are based on a network representation of Panama City's road infrastructure. Nodes represent main intersections, and paths are the distances between one intersection and the other. The fleet size forecast model consists of evaluating economic variables that affect fleet size. For fleet size, is understood as total number of freight vehicles registered in Panama City by the Vehicle Registration Office (which belongs to the Ground Transit and Traffic Authority). The model was defined with the equation generated by the regression analysis between population and fleet size. Other variables were also evaluated, but it was found that they hardly had any effect on freight vehicle population. The forecast estimations served as input for the tactical analysis. The tactical analysis used the Shortest Path Problem (SPP) approach to establish the most frequently visited nodes for a freight vehicle moving from a distributor to a supermarket. A node is visited if a vehicle passes through that node along its path from origin to destination. Nodes with the largest number of visits concentrated in the center of the City. The strategic analysis is based on the forecast model results. The fleet size per county was estimated an assigned to each node. In this analysis, fleet size is been used as a proxy for the number of trips moving in or near the area where the node is, but it does not infer on the number of truck trips (the number of times each truck moves through the node). It is assumed that a node with a large volume of fleet size has a large volume of truck moving near that zone. A Pareto analysis allowed identifying the nodes with the largest fleet size. These nodes were plotted in a map to show where most of them were concentrated. The comparison shows that urban freight vehicles movements are going from the center to the outsides of the city, following the same pattern of growth as the population, but not responding at the same pace. This analysis will allow the government to identify areas with potential freight flows and use this trend as input for urban planning decisions.